A magnetic control reconfigurable coded electromagnetic absorbing metamaterial. (5th January 2022) - Gan, Ruyi; Yu, Miao; Li, Shixu; Li, Yaping; Fang, Biao; Qi, Song
Abstract: Electromagnetic absorbing metamaterial with tunability and reconfigurability arisen as an innovative emerging scientific field has attracted huge interest in a frontier academia. Magnetorheological plastomer (MRP) has excellent electromagnetic absorption performance and magnetic-induced properties, is a suitable candidate for the development of magnetic controlled reconfigurable coded electromagnetic absorbing metamaterials. In this paper, we proposed an electromagnetic absorbing metamaterial based on thermoplastic MRP, in which polycaprolactone (PCL) and carbonyl iron particles (CIPs) are used as phase-change and magnetic absorbing elements, respectively. The arch measurement system is used to test the absorbing performance in the range of 2–18 GHz, and used digital coding to design the unit cells with regulable absorption characteristics. The value of reflection loss ( RL ) is less than −10 dB in the range of 7.44–12.2 GHz, and the minimum RL can reach −17.96 dB. Meanwhile, combined with the thermoplastic property of MRP, the structure of metamaterials can be rearranged under magnetic field. The results showed that the RL in the range of 7.28–11.60 GHz can be still less than −10 dB after the magnetic control reconfiguration. It is demonstrated that the metamaterial with magnetic control, reconfigurability and coding properties have a promising future in improving the application range and absorption and reducing interference. Graphical abstract: Image 1